Influence of the cutting-edge preparation in ceramic tools for grooving of Inconel® 718 and force prediction - Pablo Fernández-Lucio; Gorka Urbikain; Soraya Plaza; Octavio Pereira (Engineering Science and Technology, an International Journal, 2024)
The machining of slots in aeronautical turbine cases and discs is an extremely delicate operation. First, these parts require materials with excellent wear, high temperature and corrosion properties, such as the low machinability materials of the S group. Secondly, as this is one of the last turning operations, the value of the part is already considerable and any machining error can be dramatic. Traditionally, carbide tools have been the choice due to their greater safety and precision control. However, ceramic inserts offer unquestionable advantages in terms of higher cutting speeds and lower cost per part. Nonetheless, the behaviour of these cutting tools has a much narrower application interval (i.e. optimal set of cutting parameters) than carbide inserts. Machine workers need reliability. This work analyses the performance of ceramics, specifically, whiskers reinforced alumina type ceramics in the machining of grooves on Inconel® 718. Specifically, it analyses the effects of edge rounding, wear and other cutting parameters on cutting forces, and proposes a predictive model for grooving including the above parameters (rounding, wear and feed) for the first time. The validation results gave relative errors of 1.5% in the tangential component, and 4.8% in the feed component. As a result, it can be stated that the rounding radius affects more feed components than tangential ones, being, moreover, more critical to wear. Furthermore, smaller feeds and bigger cutting edge radii delay the apparition of flank wear.